2015
DOI: 10.1017/s0954579415000668
|View full text |Cite
|
Sign up to set email alerts
|

Adolescents’, mothers’, and fathers’ gendered coping strategies during conflict: Youth and parent influences on conflict resolution and psychopathology

Abstract: We observed gendered coping strategies and conflict resolution outcomes used by adolescents and parents during a conflict discussion task to evaluate associations with current and later adolescent psychopathology. We studied 137 middle-to-upper-middle class predominantly Caucasian families of adolescents (aged 11–16 years, 65 males) who represented a range of psychological functioning including normative (~1/3) sub-clinical (~1/3) and clinical (~1/3) levels of problems. Adolescent coping strategies played key … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(40 citation statements)
references
References 61 publications
2
33
0
5
Order By: Relevance
“…This interactive influence of coping and stress is in line with the hypothesized stress buffering role of active coping efforts, which may be limited at higher levels of stress (Grant et al 2003; Compas et al 2001). This finding is also consistent with prior literature showing that girls who tend to actively respond when facing interpersonal stress are protected from poor adjustment and psychopathology (Marceau et al 2014), but such active efforts may not prove as useful under more chronically stressful conditions (Compas et al 1997). Based on the present findings, messages about using active coping strategies should acknowledge that the most adaptive disposition of responding to chronic stress likely includes some degree of intrapersonal flexibility in which individuals alter responses depending on level and type of stress exposure (Aldao et al 2015).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This interactive influence of coping and stress is in line with the hypothesized stress buffering role of active coping efforts, which may be limited at higher levels of stress (Grant et al 2003; Compas et al 2001). This finding is also consistent with prior literature showing that girls who tend to actively respond when facing interpersonal stress are protected from poor adjustment and psychopathology (Marceau et al 2014), but such active efforts may not prove as useful under more chronically stressful conditions (Compas et al 1997). Based on the present findings, messages about using active coping strategies should acknowledge that the most adaptive disposition of responding to chronic stress likely includes some degree of intrapersonal flexibility in which individuals alter responses depending on level and type of stress exposure (Aldao et al 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, numerous studies have demonstrated that active coping buffers adolescents from the adverse outcomes typically associated with stressful circumstances (Dumont and Provost 1999; Herman-Stahl and Petersen 1996; Marceau et al 2014). However, whether certain coping responses can be utilized effectively also depends on the type and severity of stress exposure (Compas et al 2001; Graber and Sontag 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Among families with adolescents diagnosed with Type 1 Diabetes, collaborative communication predicted improved management of symptoms over the subsequent 12 months. By contrast, markers of non-cooperative communication, which included reciprocated hostile exchanges 32, 28 or overinvolved parenting that failed to engage the adolescent 33 , contributed to increased internalizing and externalizing symptoms.…”
Section: Parenting Practices That Facilitate Sensitive Attunementmentioning
confidence: 87%
“…Cooperative negotiation of goal conflicts increases the adolescent’s trust in the parent and the likelihood that lines of communication will be open 26, 27 . Parents’ abilities to maintain open communication have been most frequently tested with observations of how parents and adolescents discuss commonly occurring topics such as household rules, curfew, money and siblings 28 . The ability of parents to supportively summarize or acknowledge their adolescent’s point of view has been consistently associated with more cooperative communication, more relationship satisfaction and better conflict resolution 29, 26, 30 .…”
Section: Parenting Practices That Facilitate Sensitive Attunementmentioning
confidence: 99%
“…In addition, child influences have been shown to differ according to the parent's sex (Besnard et al., 2013; Marceau et al., 2015). For example, Karreman, van Tuijl, van Aken, and Deković (2008) have shown that mothers’ use of positive and negative control differed according to the child's level of effortful control, while fathers’ use of the same parenting dimensions did not.…”
Section: Introductionmentioning
confidence: 99%